Social nex[us]: reimaging public life and cohesion in Windhoek West through empowering student entrepreneurs and their sidehustles - Nankela, Junior-Steps (University of the Witwatersrand, Johannesburg, 2024)
This research report addresses urban issues in the diverse community of Windhoek West, specifically the lack of social cohesion due to inadequate public facilities and the underdevelopment of local entrepreneurial opportunities. The study proposes a community-centered marketplace designed to support local SMEs and microenterprises, including those run by students and local entrepreneurs. This marketplace aims to serve as a social hub for networking and showcasing work to the Windhoek West community and beyond. The report begins with a historical overview of community centers, setting the context for Namibia’s current urban landscape, which lacks such facilities. It then redefines the community center as a nexus, or connecting point, among community members, and explores how other typologies serve similar functions. This leads to the proposal of a market as a community center for Namibia. Windhoek West is analyzed as a transition and autonomous zone combining commerce and residence. The analysis identifies issues and opportunities for intervention, forming a framework that links these activity zones through the design of the Nex[us]. Interviews with local entrepreneurs provide insights into their brand identities and how the Nex[us] can accommodate them. The proposed Nex[us] is situated on an open space northwest of Windhoek West, along a key road connecting the city center to northern residential areas. The design features three distinct spaces: a market, a park, and a production area. These spaces are conceptually and architecturally composed to challenge the dominance of multinational corporations, foster community cohesion, and provide a collaborative environment for entrepreneurs. The design emphasizes modularity, flexibility, adaptability, and inclusivity.
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment, Wits of Architecture and Planning, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; SOCIAL NEXUS; NEXUS; COMMUNITY CENTER; SDG-4: Quality education; SDG-8: Decent work and economic growth